Employability skills : ICT competencies among fresh graduates / Zainon Haji Bibi ... [et al.]. - Haji Bibi, Zainon; Bujang, Azlina; Omar, Arenawati Sehat (2012)
Information and Communication Technologies (ICTs) have become ubiquitous with current and future social and organisational development The role of these technologies in national development is undeniably significant. Malaysia now In its journey towards vision 2020 transforming to become a developed nation were as Malaysia has changed tremendously in term of technology development Therefore, it also has change the nature of work with the use high level of technology to compete in the global market. Information and Communication Technology (ICT) is expected to pervade in all fields of studies, occupations and most important is the world of work, It is believe that ICT skills are expected to provide potential employers for the organizations since employers are looking for employees that are computer literate. A graduate who is not equipped with required skills may find difficulty to obtain employment. ICT skills is namely as one of required dimension skills to retain a job.